Report of 20th general assembly - ASEAN Inter-parliamentary organization - Asean inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 1999)
Hội nghị lần thứ 20 của tổ chức liên nghị viện ASEAN được tổ chức tại Manila, Philippines từ ngày 19-24 tháng 9 năm 1999.